PENGEMBANGAN MEDIA SMART STAIRS 3D PADA MATERI PENGUKURAN SATUAN PANJANG UNTUK SISWA KELAS IV SDN MANGGIS 2 - Febri Arinda; Bagus Amirul Mukmin; Elis Irmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by one of the difficulties faced by the fourth-grade students of SDN Manggis 2, which is the challenge of understanding the concept of length measurement units, such as conversion between kilometers, centimeters, meters, and millimeters, and difficulty in memorizing length units. This issue is caused by the use of monotonous and less interactive learning media. Based on observations from 20 students, the scores ranged from 30 to 75, and the results of a student needs survey indicated that 85% of the students expressed a strong need for learning media. Therefore, the researcher developed an innovative and engaging learning media to enhance students' understanding of length measurement units.This study aims to develop the